Effect of Maternal Age on the Mother and Neonatal health in Baghdad Maternity Hospitals - qasim, Anwar; Bahaaldeen, Ezdeen (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: to compare health of mothers and neonatal among age groups, to find out the correlation betweenage groups and mother and neonatal health.Methodology: A descriptive study was carried out at delivery rooms of three teaching hospitals in Baghdad cityfrom Feb. 28th through May. 28th, 2013. A purposive (non-probability) sample of 300 laboring women was selectedfrom delivery rooms categorized into three groups, group 1 (≤19) years, group 2 their age between (20-35) yearsold and group 3 their age (≥35) years. The data were collected through the use of constructing questionnaire, aninterview technique with mothers and reviewing their medical records as means of data collection; Thequestionnaire consist of 3 parts: (1) demographic data (2) health of mothers during pregnancy (pregnancycomplications) (3) neonate health status. The validity of the study questionnaire was determined through a panelof experts and the reliability of the study questionnaire was determine by the application of pilot study.Descriptive statistical analysis procedure (frequencies and percentages) and inferential data analysis procedure(chi-square, P-value, split- half approach and Cronbach's Alpha correlation coefficients) were applied for dataanalysis.Results: the finding of the study indicated that the highest percentages of all the study groups were primary schoolgraduates, urban and housewives. More than half of mothers in group 1 (teenage mothers) and group 2 (20-35)years were related to their husband, while the highest percentages of mothers in group 3 (advanced maternal age)were not related to their husband. The highest percentages of complications present in group 1 (teenage mothers)were anemia, urinary tract infection, multiple pregnancy, Oligohydramnios, poly-hydramnios, intra uterine growthretardation, Post-term labor, low Apgar score, low birth weight, congenital anomalies, respiratory distreessyndrome, meconium aspiration syndrome and neonatal death. The highest percentages of complications presentin group 3 (advanced maternal age) were pregnancy induced hypertension, gestational diabetes, antepartumhaemorrhage, pre-term labor, premature rupture of membrane and macrosomia. There is a statistical significantcorrelation between age groups and hypertension and preterm, Apgar score, neonatal weight and respiratorydistress syndrome.Recommendations: Care providers need to be aware about the increasing of obstetrical and neonatal healthcomplications in the extremities of maternal age (teenage and advanced maternal age) and adjust obstetrical andneonatal management protocols to ensure optimal maternal and neonatal health